RIJANG DAN PEMANFAATANNYA SEBAGAI ALAT BATU - Cahyaningtyas, Yuka Nurtanti (Naditira Widya, 2010)
Based on bibliographical studies on stone tools which have intensively analyzed by Pusat Penelitian dan Pengembangan Arkeologi Nasional and its centres,it can be inferred that raw materials used to make stone tools are mostly chert. Geologically, this is understandable, since chert is one of the sedimentary rocks originated from the permo-carbon stage which were specifically sedimented in Kalimantan. Such rock is usually structured in the deep sea by a hydrothermal action in forms of aggregate limestone concretion and hematite. Chert is commonly found in rivers and limestone hills. The physical hardness of chert is 7, which makes chert flakes favorable to use in cutting, slicing or incising softer subject. Therefore, I assume that chert was chosen stone tools raw material by human in the past due its physical quality and effortlessness to find it in rivers close to human dwellings. This article discusses the technology of making stone tools of chert focusing on the geology of the site, the environment where chert was formed and its physical attributes